2017
DOI: 10.1001/jama.2017.10981
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Laparoscopic Antireflux Surgery and Recurrence of Gastroesophageal Reflux

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
2
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 36 publications
1
70
2
8
Order By: Relevance
“…In addition, there is a paucity of data on identifying preoperative factors that predict successful outcomes after MSA. 13 Such data can be used to guide and refine patient selection and improve preoperative patient counseling for the purpose of maximizing successful outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is a paucity of data on identifying preoperative factors that predict successful outcomes after MSA. 13 Such data can be used to guide and refine patient selection and improve preoperative patient counseling for the purpose of maximizing successful outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of reflux was based on the long‐term use of anti‐reflux medication, made prospectively through the use of data in a high‐quality and nationwide complete drug register, which allowed for accurate assessment of the outcome and complete follow‐up for several years. Use of anti‐reflux medication as the definition of reflux symptoms allows for an unbiased assessment of reflux and has been used successfully in previous research . This definition does not require subjective reporting by the participants or objective measures and thus allows for a register‐based study approach, enabling a large cohort with long and complete follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment effect observed in this study was immediate and durable, it was insufficient in about half of all patients. For comparison, the proportion of patients requiring anti‐reflux medication after fundoplication is <10% in the first year . However, a direct comparison to treatment results from fundoplication may be inadequate given that the main indication for gastric bypass is obesity; the preoperative work‐up of GERD may be limited, and many patients with GERD undergoing gastric bypass may not have objective findings of reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for recurrence of reflux were female gender, older age and comorbidity. 7 A 5-year follow-up study, the LOTUS trial (Long-Term Usage of Esomeprazole vs Surgery for Treatment of Chronic Gastro-oesophageal Reflux Disease), demonstrated that a standardised laparoscopic Nissen fundoplication performed in expert centres and treatment with esomeprazole had similar outcome results concerning treatment failure rate, although that relief of heartburn was somewhat superior after surgery. The vast majority of patients achieved and remained in remission after 5 years, both in the surgical group as well as in the medical treatment group.…”
Section: What Are the New Findings?mentioning
confidence: 99%